RE-PURCHASING TRENDS OF IAIN LHOKSEUMAWE'S FEBI STUDENTS FROM 'SHOPEE': EXPLORING PRODUCT QUALITY, PRICES, AND PROMOTIONS FOR THE BEST DEALS - Yoesoef, Yoesrizal Muhammad; Iskandar; Ayyuma, Churatul (IAIN Lhokseumawe, 2023)
This study intends to investigate the interaction of product quality, price, and promotion on the desire to repurchase in the Shopee market. Using online surveys sent to 92 respondents, it also aims to evaluate how product grade, pricing, and promotional efforts positively influence repurchase interest among students at the Islamic Business and Finance Faculty (FEBI). The study used quantitative methodologies, and the questionnaire had seven questions total, with seven questions each about the product quality, pricing, promotion, and desire to repurchase. Numerous statistical tests were used, such as testing for the validity and reliability of the hypotheses, conventional assumption tests, multiple linear regression analysis, T-tests, F-tests, and determination square tests (R2). The results of the F test showed that all three variables—product quality, price, and promotion—cooperately affect repurchase interest in the Shopee marketplace. In addition, the T-test results showed that product quality has a large impact on repurchase attractiveness, whereas price and promotion had less of an impact on shoppers' desire to make a second purchase on Shopee.